Correlation between heart rate variability indexes and aerobic physiological variables in patients with COPD. Issue 2 (9th November 2014) - Leite, Marceli R.; Ramos, Ercy Mara C.; Kalva‐Filho, Carlos A.; Rodrigues, Fernanda Maria M.; Freire, Ana Paula C.F.; Tacao, Guilherme Y.; de Toledo, Alessandra C.; Cecílio, Michel J.; Vanderlei, Luiz Carlos M.; Ramos, Dionei
Abstract Background and objective Previous studies have shown a relationship between the level of physical fitness and autonomic variables. However, these relationships have not been investigated in patients with chronic obstructive pulmonary disease (COPD). The objective of this study was to correlate the resting heart rate variability (HRV) indexes with aerobic physiological variables obtained at a maximal exercise test in patients with COPD. Methods Thirty‐seven patients with COPD (63 (59–70) years; 46 (35.4–63.7) forced expiratory volume in 1 s (FEV1)%) underwent assessment of autonomic modulation at rest for 20 min to determine the HRV indexes in time and frequency domains. Soon after that, the patients performed an incremental exercise test to determine the anaerobic threshold (GET), the peak oxygen uptake (VO2PEAK) and the velocity corresponding to VO2PEAK (vVO2PEAK). Results The indexes that express parasympathetic component as RMSSD (11.4 [7.5–23.8], HF (ms2) (35 [17–195] and SD1 (8.1 [5.3–16.8]), correlated with GET (r = 0.39; r = 0.43; r = 0.39 respectively). The indexes that represent the overall variability, SDNN (19.5 [13.9–28.8]), LF (ms2) (111 [38–229]), and SD2 (26.8 [18.6–35.4]) correlated with vVO2PEAK (r = 0.37; r = 0.38; r = 0.37; r = 0.44; r = 0.43; r = 0.46 respectively). Likewise, the indexes LF (ms2), LF (nu) (63.2 [46–77, 9]), HF (nu) (36.8 [22.1–54]), and LF/HF (1.7 [0.9–3.5]) correlated with VO2PEAK (r = 0.35; r = 0.35; r = −0.35; r = 0.40 respectively). Conclusions This study demonstrated that HRV indexes at rest may become a predictive tool for aerobic capacity in COPD patients after the development of more consistent methods.